Empowering Communities In Efforts To Accelerate Stunting Reduction In Watusampu Village Palu City - Muhammad Sabri Syahrir; Amilah Eka Putri; Herbourina Bonita, A. Ferina (Sean Institute, 2024)
Stunting, characterized by shorter height or length in children under five compared to their peers, has seen a decrease in Palu City from 24.7% in 2022 to 22.1% in 2023. Despite various efforts, stunting remains high in Indonesia. An effective approach is community empowerment through nutrition and health assistance for pregnant women and stunted children. This support aims to educate and help families at risk of stunting in meeting their nutritional and health needs to prevent stunting. The program involved direct visits by community members, health teams, and posyandu cadres to homes and Posyandu. Results showed increased knowledge and improvements in height and weight for stunted children and pregnant women. However, the program has not fully met its targets due to low awareness among mothers and families about healthy, balanced nutrition. Additional strategies are needed, including more intensive training and counseling, enhanced social support, and closer collaboration to boost awareness and behavior changes related to diet and health.